Sanctioning Capacity in Trade and Sustainability Chapters in EU Trade Agreements: The EU–Korea Case - García, María J. (2022)
Although sanctions targeting political regimes receive the most media attention, the EU can also sanction states for labour rights violations through its trade policy. Although in practice such sanctions are applied only in extreme cases, the possibility of suspending trade preferences increases the EU’s leverage. In modern trade agreements, the EU incorporates Trade and Sustainable Development (TSD) chapters for labour and environmental matters. However, trade sanctions for non-compliance with this chapter are absent. Instead, a dedicated dispute settlement arrangement exists, leading to recommendations by a panel of experts. In 2019 the EU launched proceedings against South Korea for failing to uphold commitments to ratify and implement International Labour Organisation core conventions regarding trade unions under the 2011 EU–Korea Trade Agreement. In 2021, the panel of experts sided with the EU’s interpretation of commitments under the TSD chapter. This initial case represents the EU’s intention to focus on the implementation of TSD chapters. Using data from official documents, this article process-traces the dispute with Korea. It argues that the outcome of the case, and Korea’s ratification of fundamental International Labour Organisation conventions in 2021, demonstrate the potential of the TSD chapter, when forcefully enforced, to partially redress the weak sanctioning capacity in TSD chapters. It also uncovers important caveats regarding state capacity and alignment with government objectives as conditioning the effectiveness of TSD chapters’ non-legally binding sanctioning mechanisms.